Online media planning: getting the strategy and targeting right - Sheldon, Nigel (Henry Stewart Talks, 2009)
Online media campaign development, Customer purchase funnel, Business background and objectives, Consumer insights, Strategic framework, Targeting, Creative implications, Implementation, Accountability
Archived at 2022/04/11